A hierarchical dispatch strategy of hybrid energy storage system in internet data center with model predictive control. (1st February 2023) - Wang, Kaifeng; Ye, Lin; Yang, Shihui; Deng, Zhanfeng; Song, Jieying; Li, Zhuo; Zhao, Yongning
Highlights: An analysis model for dynamic available energy of UPS in IDC is proposed. Integrated dispatching strategy of the UPS and conventional units. A reallocation method based on dispatching error and SOC of BESS improve the optimization of SOC and the revenue of the IDC increased by about ¥5950. Proposed strategy increases UPS utilization by about 85% and reduces the MAE and RMSE of the SOC fluctuation to 12%-19%. Abstract: The internet data center (IDC) can improve the stability of power system and increase the utilization of uninterruptible power supply (UPS) with battery energy storage system (BESS) and hydrogen fuel cell (HFC) by participating in dispatch operations. This paper proposes a hierarchical dispatch strategy assisted by model predictive control (MPC) for UPS in IDC including available energy analysis, the upper-level power system dispatch strategy and the lower-level IDC dispatch strategy. The data security can be ensured through available energy analysis based on load forecasting information of IDC. Then, the upper-level dispatch model aims at increasing the utilization of UPS and the revenue of IDC via minimizing the total generation cost. Meanwhile, the lower-level dispatch method with MPC reallocates the upper-level dispatch instructions between BESS and HFC by balancing power tracking error and the state of charge of BESS. Finally, the effectiveness of the strategy is verified by several experiments in MATLAB platform. Numerical results show that the proposed strategy increases the utilization rate of the UPS by about 85% and the revenue by about ¥5950, and the SOC fluctuation is reduced to 12%-19%.